Macrophage-mediated IL-6 signaling drives ryanodine receptor-2 calcium leak in postoperative atrial fibrillation - Keefe, Joshua Anthony; Aguilar-Sanchez, Yuriana; Navarro-Garcia, J. Alberto; Ong, Isabelle; Li, Luge; Paasche, Amelie; Abu-Taha, Issam; Tekook, Marcel A.; Bruns, Florian; Zhao, Shuai; Kamler, Markus; Shen, Ying H.; et al. (The journal of clinical investigation, 2025)
Macrophage-mediated IL-6 signaling drives ryanodine receptor–2 calcium leak in postoperative atrial fibrillation Joshua A. Keefe, Yuriana Aguilar-Sanchez, J. Alberto Navarro-Garcia, Isabelle Ong, Luge Li, Amelie Paasche, Issam Abu-Taha, Marcel A. Tekook, Florian Bruns, Shuai Zhao, Markus Kamler, Ying H. Shen, Mihail G. Chelu, Na Li, Dobromir Dobrev, Xander H.T. WehrensJ Clin Invest. 2025;135(9):e187711. https://doi.org/10.1172/JCI187711. Postoperative atrial fibrillation (poAF) is AF occurring days after surgery, with a prevalence of 33% among patients undergoing open-heart surgery. The degree of postoperative inflammation correlates with poAF risk, but less is known about the cellular and molecular mechanisms driving postoperative atrial arrhythmogenesis. We performed single-cell RNA-seq comparing atrial nonmyocytes from mice with and without poAF, which revealed infiltrating CCR2+macrophages to be the most altered cell type. Pseudotime trajectory analyses identified Il-6 as a gene of interest driving in macrophages, which we confirmed in pericardial fluid collected from human patients after cardiac surgery. Indeed, macrophage depletion and macrophage-specific Il6ra conditional knockout (cKO) prevented poAF in mice. Downstream STAT3 inhibition with TTI-101 and cardiomyocyte-specific Stat3 cKO rescued poAF, indicating a proarrhythmogenic roleof STAT3 in poAF development. Confocal imaging in isolated atrial cardiomyocytes (ACMs) uncovered what we believe to be a novel link between STAT3 and CaMKII-mediated ryanodine receptor–2 (RyR2)-Ser(S)2814 phosphorylation. Indeed, nonphosphorylatable RyR2S2814A mice were protected from poAF, and CaMKII inhibition prevented arrhythmogenic Ca2+ mishandling in ACMs from mice with poAF. Altogether, we provide multiomic, biochemical, and functional evidence frommice and humans that IL-6-STAT3-CaMKII signaling driven by infiltrating atrial macrophages is a pivotal driver of poAF, which portends therapeutic utility for poAF prevention.
Gesehen am 10.12.2025